Discontinuities and disruptions in drug dosage guidelines for the paediatric population. (21st February 2018) - Chitty, Kate M.; Chan, Bosco; Pulanco, Camille L.; Luu, Sonya; Egunsola, Oluwaseun; Buckley, Nicholas A.
Abstract : Aims: This study investigates paediatric drug dosage guidelines with the aim of investigating their agreement with body surface area (BSA) scaling principles. Methods: A total of 454 drug dosage guidelines listed in the AMH‐CDC 2015 were examined. Data extracted included the administration, frequency and dose per age bracket from 0 to 18 years. Drug treatments were categorized as follows: (1) The same dose recommendation in milligrams per kilogram (mg kg −1 ) for all age/weights; (2) Change in the mg kg −1 dosing according to age/weight; (3) Change in dose in mg according to age/weight; (4) Change from mg kg −1 dosing to a dose in mg according to age/weight; (5) The same recommendation for all age/weight groups in mg; or (6) BSA dosing. Example drugs were selected to illustrate dose progression across ages. Results: Most drug treatments (63%) have the same mg kg −1 dose for all age/weight groups, 14% are dosed in mg kg −1 across all ages with dose changes according to age/weight, 13% were dosed in mg across all ages with dose changes, 10% switched from mg kg −1 to a set dose in mg, 4.2% have the same dose in mg for all age and weight groups and 2.2% are dosed according to BSA. Conclusions: Paediatric dosage guidelines are based on weight‐based formulas, available dosing formulations and prior patterns of use. Substantial variation from doses predicted by BSA scaling are common, as are large shifts in recommended doses at age thresholds. Further research is required to determine if better outcomes could be achieved by adopting biologically based scaling of paediatric doses.